Understanding Public Attitudes Toward Cannabis Legalization: Qualitative Findings From a Statewide Survey. (3rd July 2019) - Resko, Stella; Ellis, Jennifer; Early, Theresa J.; Szechy, Kathryn A.; Rodriguez, Brooke; Agius, Elizabeth
Abstract: Background : Cannabis policy is rapidly evolving in the United States as more states legalize medical and non-medical marijuana. Public opinion has shifted dramatically in favor of marijuana legalization. Objectives : This study examines the reasons that people support, oppose, or are unsure about marijuana legalization, focusing on the participants' own words. Methods : A statewide sample of adults ( N  = 2, 608) in Michigan completed an online survey about marijuana legalization (August and September 2016). Participants indicated whether they supported, opposed, or were unsure about marijuana legalization, and were then prompted to complete an open-ended response explaining the main reasons for their view. Thematic analysis was then used to code the open-ended responses ( n  = 2, 054) and analytic induction was used to evaluate the coding. Results : 48.1% of the sample supported cannabis legalization, 41.9% were opposed to legalization, and 10% were unsure. Harms associated with marijuana use were the most commonly given reasons for opposing legalization. Those who supported legalization were most likely to state that marijuana is less dangerous than other substances and has medical benefits. They also cited criminal justice reform and the potential for tax revenue as potential benefits of legalization. Reasons for supporting and opposing legalization differed based on gender, age, and recent marijuana use. Conclusions/Importance : Findings highlight nuances in public attitudes toward cannabis legalization. Many who support cannabis legalization recognize some potential negative consequences of these policy changes. Understanding views of cannabis is important as policies for marijuana use and sales become less restrictive.